A Review of Maritime Nuclear Reactor Systems - Keith E. Holbert (Journal of Nuclear Engineering, 2025)
Marine reactors have been applied to floating nuclear power plants, naval vessels such as submarines, and civilian ships such as icebreakers. Nuclear-powered shipping is gaining increased interest because of decarbonization goals motivated by climate change. Enhanced reactor safety can potentially reduce regulatory and liability challenges to the adoption of nuclear propulsion systems for merchant ships. This gives strong impetus for reviewing past use of nuclear reactor systems in marine environments, especially from the perspective of any accident scenarios, lest planners be caught unaware of historical incidents. To that end, a loss of coolant accident (LOCA) in a Lenin icebreaker reactor in 1965 and disposal at sea of some of its damaged fuel and reactor vessel as well as the entire tri-reactor compartment is recounted.